Distribution of Droplets and Immune Responses After Aerosol and Intra-Nasal Delivery of Influenza Virus to the Respiratory Tract of Pigs - Martini, Veronica; Hinchcliffe, Michael; Blackshaw, Elaine; Joyce, Mary; McNee, Adam; Beverley, Peter; Townsend, Alain; MacLoughlin, Ronan; Tchilian, Elma (Frontiers in Immunology, 2020)
Recent evidence indicates that local immune responses and tissue resident memory T cells (TRM) are critical for protection against respiratory infections but there is little information on the contributions of upper and lower respiratory tract (URT and LRT) immunity. To provide a rational basis for designing methods for optimal delivery of vaccines to the respiratory tract in a large animal model, we investigated the distribution of droplets generated by a mucosal atomization device (MAD) and two vibrating mesh nebulizers (VMNs) and the immune responses induced by delivery of influenza virus by MAD in pigs. We showed that droplets containing the drug albuterol, a radiolabel (99mTc-DTPA), or a model influenza virus vaccine (S-FLU) have similar aerosol characteristics. 99mTc-DTPA scintigraphy showed that VMNs deliver droplets with uniform distribution throughout the lungs as well as the URT. Surprisingly MAD administration (1ml/nostril) also delivered a high proportion of the dose to the lungs, albeit concentrated in a small area. After MAD administration of influenza virus, antigen specific T cells were found at high frequency in nasal turbinates, trachea, broncho-alveolar lavage, lungs, tracheobronchial nodes, and blood. Anti-influenza antibodies were detected in serum, BAL and nasal swabs. We conclude that the pig is useful for investigating optimal targeting of vaccines to the respiratory tract.